PRAKTEK JUAL BELI PERHIASAN EMAS DENGAN SISTEM TUKAR TAMBAH MENURUT HUKUM ISLAM (STUDI KASUS DI TOKO SINAR JAYA KACAMATAN TANGGUL KABUPATEN JEMBER) - Umi Karimatul Azizah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
Abstract: Islam is a perfect and universal religion, containing teachings that guarantee the benefit of human life, both in this world and the hereafter. What is taught in Islam is not only specific to certain people, because the teachings of Islam encompass all human beings who exist on this earth. The contents of the teachings were not only discussing and regulating certain fields, or merely regulating human relations with his creator, but also regulating human relations with fellow human beings themselves. The problem formulation of this research is: 1) the practice of buying and selling gold jewelry with an exchange system in the Sinar Jaya store Tanggul District, Jember Regency 2) buying and selling gold with an exchange system according to Islamic law in the Sinar Jaya store, the Tanggul District, Jember Regency. This study uses empirical juridical research with a case study approach, this research data source is a primary data source with secondary data collection methods by interviewing, observing and documenting, the research results are followed by data analysis with stages of editing, classifying, verifying, analizing, and concluding. The data validity technique is done by extending the observation and trialing. The results of this study can be concluded that, the first practice of buying and selling gold jewelry with an exchange system in the Sinar Jaya store Kagamatan embankment, Jember Regency is one of the precious metals coveted by humans, categorized as a precious metal because it has a character that makes it more valuable than other metals. The Second Practice of Buying and Selling Gold with an Exchange-Adding System According to Islamic Law Exchange-Adding is exchanging goods by giving additional money between the seller and the buyer in the transaction of buying and selling gold jewelry, which can be said to exchange the goods they have. The buyer gives additional money by paying the difference in price between the gold jewelry that you want to buy from the seller and the buyer previously had.